COVID-19 and APOL-1 High-Risk Genotype-Associated Collapsing Glomerulonephritis - Sasmit Roy; Srikanth Kunaparaju; Narayana Murty Koduri; Vikram Sangani; Mytri Pokal; Venu Madhav Konala; Mamtha Balla; Sreedhar Adapa (Case Reports in Nephrology)
Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) primarily affects the lungs and can lead to acute respiratory distress syndrome (ARDS). The ongoing global pandemic has created healthcare and economic crisis for almost every nation of the world. Though primarily affecting the lungs, it has also affected the kidney in various ways including acute kidney injury (AKI), proteinuria, and hematuria. It has been increasingly shown that African American (AA) individuals affected with COVID-19 and presenting with AKI and nephrotic-range proteinuria are very susceptible to focal segmental glomerulosclerosis (FSGS). The APOL-1 gene, associated with the African American population, has been increasingly recognized as a risk factor for FSGS affected with COVID-19. Our case highlights a similar case of COVID-19 in a 65-year-old AA descendant with biopsy-proven FSGS and genetically confirmed APOL-1 alleles.